Implementação da disciplina de libras nas licenciaturas em município do interior de São Paulo - Costa, Otávio Santos (2015)
Experienced in recent decades important legislative advances regarding the rights of persons with disabilities, especially the right to education. In this context, deaf education is contemplated from the recognition of their language features by Law No. 10436 of 2002 ( Law Libras ) and Decree No. 5626/2005 , which regulates provides for bilingual education for the deaf and the means for their development , including the insertion of Libras of discipline in teacher training courses. This study aimed to investigate the implementation process of Libras discipline in Undergraduate courses of higher education institutions in medium-sized city in the state of São Paulo. It was decided to carry out a qualitative research of descriptive nature, conducted with the two public universities, one federal and one state, and a university center of private initiative divided into three parts: Study I, analysis of documents characterization of disciplines of Libras; Study II , interviews with managers and teachers involved in the implementation process of the Libras discipline ; III study , focus groups with graduates of Libras disciplines of the institutions surveyed . All individuals participating in the study signed the Informed Consent Statement. The results point to the strong resistance of the institutions surveyed front to effect of the propositions of the Decree No 5626 /2005 , but also indicate that although separate the process of its implementation contexts, Libras disciplines seem to be heading for a consolidation with features to collaborate for the training of future teachers with respect to the proposed legislation to deaf education.